Taper wear in total joint arthroplasty can be reliably assessed with various coordinate measuring systems - Bormann, Therese; Müller, Ulrike; Sonntag, Robert; Schröder, Stefan; Kretzer, Jan Philippe (Scientific reports, 2025)
In total joint arthroplasty, wear and corrosion at modular taper junctions is an issue with clinical implications, as ions and wear debris can lead to adverse tissue reactions. The quantification of the generated wear is, therefore, an important measure to judge the performance of such modular junctions. This applies to pre-clinical in vitro investigations as well as to retrospective investigations of retrieved implants. The volume of the worn material can be determined with coordinate measuring machines (CMMs), which can generally be classified as tactile and optical systems. The study aims on the comparison of a tactile with two optical CMM systems for the determination of taper wear. To do so, four taper samples—three trunnions and one bore taper—with different amounts of known volumetric wear (range 1.5 mm3 to 8.3 mm3) were fabricated. Wear volume, linear deviation and taper angle were determined with the different CMM systems. The tactile system yielded the highest deviation from the gravimetric reference values of about 0.3 mm3, while the optical systems exhibited deviations of about 0.1 mm3 and 0.2 mm3. Clinically relevant taper wear, however, is well measurable with all investigated systems.